Rumah, Tempat Kembali: Pemaknaan Rumah pada Mahasiswa Rantau - Prasetio, Clement Eko; Sirait, Esther Gustara Nadine; Hanafitri, Aulia (Mediapsi, 2020)
Regional students (Indonesian: Mahasiswa rantau) are individuals who should move away from home to study in other cities, who are highly likely to experience feelings of homesickness. In this research, we aimed to understand what causes regional studentsâ€™ homesickness and what the meanings of home for them are. Participants in this research were 15 regional students from the Faculty of Psychology, Padjadjaran University, who were recruited through convenience sampling. This research was designed as a qualitative study with a phenomenological approach. Data in this research, which were drawn from in-depth interviews, revealed eight themes related to regional studentsâ€™ homesickness. These themes included feelings, activities, routines, food, pets, family and friends, home atmosphere, and rooms. Additional findings uncovered two meanings of homesickness for regional students, that is, â€œhome is feelingsâ€ and â€œhome is familyâ€. Empirical findings in this research provide a useful insight into the prevention of regional studentsâ€™ homesickness, by focusing on the meanings of home and efforts to provide new environment for those students.Mahasiswa rantau merupakan individu yang harus meninggalkan daerah asal untuk menuntut ilmu di kota lain, yang sangat mungkin mengalami perasaan rindu rumah atau homesickness. Penelitian ini bertujuan untuk memahami berbagai hal sebagai sumber homesickness dan makna rumah bagi mahasiswa rantau. Subjek penelitian adalah 15 mahasiswa rantau Fakultas Psikologi Universitas Padjadjaran, yang direkrut melalui convenience sampling. Penelitian menggunakan metode kualitatif dengan pendekatan fenomenologi. Hasil penelitian atas dasar wawancara mendalam dengan subjek penelitian menemukan delapan tema yang terkait dengan homesickness mahasiswa rantau, yaitu perasaan, aktivitas, rutinitas, makanan, hewan peliharaan, keluarga dan teman, suasana rumah, serta kamar. Temuan lain mengungkap dua makna rumah bagi mahasiswa rantau, yaitu â€œrumah adalah perasaanâ€ dan â€œrumah adalah keluargaâ€. Hasil penelitian ini dapat digunakan sebagai acuan untuk pencegahan homesickness pada mahasiswa rantau, dengan fokus pada makna rumah bagi mereka dan upaya menyediakan lingkungan baru mereka.Â